The Effect of Pyrroloquinoline Quinone on the Expression of WISP1 in Traumatic Brain Injury - Yongqi Ye; Pengju Zhang; Yuhang Qian; Baoxin Yin; Meijuan Yan (Hindawi Limited, 2017)
WISP1, as a member of the CCN4 protein family, has cell protective effects of promoting cell proliferation and inhibiting cell apoptosis. Although some studies have confirmed that WISP1 is concerned with colon cancer and lung cancer, there is little report about the influence of WISP1 in traumatic brain injury. Here, we found that the expression of WISP1 mRNA and protein decreased at 3 d and then increased at 5 d after traumatic brain injury (TBI). Meanwhile, immunofluorescence demonstrated that there was little colocation of WISP1 with GFAP, Iba1, and WISP1 colocalized with NeuN partly. WISP1 colocalized with LC3, but there was little of colocation about WISP1 with cleaved caspase-3. Subsequent study displayed that the expression of β-catenin protein was identical to that of WISP1 after TBI. WISP1 was mainly located in cytoplasm of PC12 or SHSY5Y cells. Compared with the negative control group, WISP1 expression reduced obviously in SHSY5Y cells transfected with WISP1 si-RNA. CCK-8 assay showed that pyrroloquinoline quinone (PQQ) had little influence on viability of PC12 and SHSY5Y cells. These results suggested that WISP1 played a protective role after traumatic brain injury in rats, and this effect might be relative to autophagy caused by traumatic brain injury.